Going beyond children's single‐text comprehension: The role of fundamental and higher‐level skills in 4th graders' multiple‐document comprehension. (9th May 2019) - Florit, Elena; Cain, Kate; Mason, Lucia
Abstract : Background: Children's comprehension of single texts relies on both foundational and higher‐level skills. These are also assumed to support multiple‐document comprehension, but their relative importance has not been examined, to date. Multiple‐document comprehension additionally requires the identification and use of information about each document's source. Aims: This study examined multiple‐document comprehension in primary school‐aged children. It sought to determine the relative importance of skills proposed to be common to both single‐text and multiple‐document comprehension (word reading fluency, verbal working memory, comprehension monitoring) and specific to the latter (source use). Single‐text comprehension and prior topic knowledge were considered as moderator and control. Sample: Participants were 94 children in the fourth year (mean age = 9; 7 years; 52% females). Methods: Children read three documents on each of two topics (chocolate and video games). Multiple‐document comprehension and source use were assessed through short essays. Independent measures of the fundamental and higher‐level skills were used. Results: There was a significant direct and indirect influence of word reading fluency on comprehension of multiple documents on videogames and also an indirect influence of comprehension monitoring. Indirect influences of word reading fluency and comprehension monitoring on multiple‐document comprehension for both topics were also apparent. Verbal working memory was not a unique predictor. When source information was identified, it was included to support the argument in the composition. Conclusions: Efficient word reading, comprehension monitoring, and single‐text comprehension are important for multiple‐document comprehension in young readers. Implications of these findings and differences between the two document sets are discussed.